Hydroxyapatite-based materials for adsorption, and adsorptive membrane process for heavy metal removal from wastewater: Recent progress, bottleneck and opportunities - Suriani binti Abu Bakar (Tanjung Malim, 2024)
Hydroxyapatite-based materials for adsorption, and adsorptive membrane process for heavy metal removal from wastewater: Recent progress, bottleneck and opportunities by Suriani binti Abu Bakar